The contradictions of legalised gambling and dealing with problem gambling in Singapore - Oh, Pierluca (2014)
This paper looks into the link between the state and the gambling sector in Singapore, focusing specifically on the treatment of problem gambling. I look into how the legalisation of gambling by the state contrasts its desires and efforts to mitigate problem gambling. I argue that the state manages this conflict of interests through the dissemination of specific discourses through various institutions, in line with Foucault’s concept of governmentality. Additionally, I consider how the success of the state in the displacing of responsibility onto individuals for gambling activities works against its efforts against problem gambling, due to the nature of problem gamblers.